Sovereign debt diplomacies: Rethinking sovereign debt from colonial empires to hegemony - Pierre Pénet; Juan Flores Zendejas (Oxford University Press, 2021)
This volume offers two important contributions to the literature on sovereign debt. First, it provides a unique genealogy of debt collection practices in terms of their availability, acceptability and efficacy. We argue that creditors' tactics and methods to enforce debt repayment emerged and solidified to a large extent in relation to the threads of colonial history, from the building of empires to the decolonisation era. Second, this volume reflects critically on the relevance of neo-colonial interpretations in recent cases of sovereign debt disputes
Keywords: 330; Sovereign debt; debt defaults; debt restructurings; legal clauses; bondholder committees; World War 2; colonial history; informal empires; odious debt; hegemony